Hormonal strategies for follicular atresia induction and stimulation of emergence of a new follicular wave in mares - Reway, Ana Paula (2021)
The development of a hormonal protocol capable of estrus synchronization and time- fixed ovulation induction in mares has been a challenge. The two main difficulties to achieve it are to promote follicular atresia and to induce the emergence of a new synchronic follicular wave among treated mares. Previous studies from our laboratory were capable, for a few days, to stop follicular growth with no occurrence of atresia and posterior reestablishment of the follicular growth. This condition did not permit a similar follicular development among the mares to permit only one treatment to induce ovulation in a fixed-time manner. The main objectives of this project were: (1) to develop a hormonal protocol capable to promote follicular atresia, and (2) the emergence of a synchronic follicular wave in mares. Five experiments were performed: Chapter 3: Experiment 1 Daily plasma progesterone (P4) concentration curve in ovariectomized and cyclic mares treated with an intravaginal P4 releasing device. Experiment 2 Evaluation of six hormonal protocols for atresia induction and synchronization of a new follicular wave. Experiment 3 Test of two modified hormonal protocols for follicular atresia induction and synchronization of a new follicular wave. Chapter 4: Experiment 4 - Evaluation of plasma P4 levels and functional status of the corpus luteum (CL) using Doppler ultrasonography in cyclic mares submitted to treatments using different sources of exogenous P4. Chapter 5: Experiment 5 - Test of the efficiency of fixed-time ovulation induction and fertility in cyclic mares submitted to hormonal protocols for follicular wave and ovulation synchronization. It was hypothesized that the degree of synchrony of follicular growth would dependent on the efficiency obtained for induction of follicular atresia by the hormonal treatment performed. Besides, it was hypothesized that luteal function of CLs resulting from ovulations post-hormonal treatments would present high degree of vascularization and consequently the mares would present high plasmatic levels of P4. Another hypothesis was that it would be possible to perform fixed time artificial insemination in mares and its oocytes submitted to hormonal treatment for synchronization of estrus and ovulation would be fertile. The effect of new sources of hormonal combinations of P4 and estradiol and the association of low doses of hCG and deslorelin were tested during two reproductive seasons. Two of the previously tested hormonal protocols were selected based on their efficiency for new studies of fertility (Chapter 5; Experiment 5). The first protocol promoted follicular atresia and the oocytes were originated from follicles emerged from a new follicular wave. The second protocol was not capable to promote neither atresia nor the emergence of a new follicular wave, however caused follicle growth suppression and ovulation of follicles that resumed its growth after exogenous P4 source removal. The luteal function post-hormonal treatments remained with a good capacity of P4 production. The fertility of mares submitted to hormonal treatment protocols for ovulation synchronization, after fixed time artificial insemination 30 hours after ovulation induction, was evaluated by ultrasound diagnosis of gestation thirteen days after ovulation. Pregnancy rates were 83% (15/18) and 72% (13/18), on both treatments and were not statistically different (P > 0.05). Nevertheless, the average diameter of the embryonic vesicles in the group not capable of causing follicular atresia was smaller than in the group that showed follicular atresia (P < 0.05), and even smaller than the average reported in the literature on the thirteenth day of gestation. Initial embryonic development may have been compromised when the oocytes resulted from follicles which presented suppressed growth by the action of exogenous P4. Therefore, the hormonal strategies used were able to develop two hormonal treatment protocols capable of synchronizing ovulations for fixed time artificial insemination in mares presenting satisfactory pregnancy rates.